Roles of retinoic acid-related orphan receptor α in high glucose-induced cardiac fibroblasts proliferation - Wenqing San; Qianyou Zhou; Danning Shen; Danyi Cao; Yun Chen; Guoliang Meng (Frontiers in Pharmacology)
Diabetic cardiomyopathy, characterized by myocardial fibrosis, is a common complication of diabetes. Retinoic acid-related orphan receptor α (RORα) participates in various pathological and physiological cardiovascular processes. The current research aims to elucidate the roles and mechanisms of RORα in high glucose induced cardiac fibroblasts proliferation. Primary neonatal cardiac fibroblasts were isolated from Sprague-Dawley rats, and pre-administrated with RORα antagonist SR3335 (20 µM) or RORα agonist SR1078 (10 µM) followed by the stimulation with normal glucose (5.5 mM) or high glucose (33.3 mM) respectively. Lactate Dehydrogenase (LDH) release into culture medium, cellular adenosine-triphosphate (ATP), and cell number were detected. Expressions of Collagen I, Collagen III, proliferating cell nuclear antigen (PCNA), α-smooth muscle actin (α-SMA), receptor-interacting protein kinase 1 (RIPK1) and receptor-interacting protein kinase 3 (RIPK3) were evaluated. The extent of oxidative stress was also assessed. Our study found that high glucose elevated LDH release, reduced cellular ATP production, increased cells numbers, elevated expression of Collagen I, Collagen III, PCNA, α-SMA, RIPK1 and RIPK3, decreased mitochondrial membrane potential, strengthened intensity of dihydroethidium (DHE) and MitoSOX fluorescence. Above effects were all further exacerbated by SR3335 but significantly reversed by SR1078. In conclusion, RORα antagonist SR3335 promoted cell injury and proliferation, enhanced collagen synthesis, facilitated oxidative stress and necroptosis in cardiac fibroblasts with high glucose stimulation, whereas RORα agonist SR1078 showed opposing effects. Our study proposed RORα as a novel target against high glucose-induced cardiac fibroblasts proliferation, which is beneficial to clarify ideal therapeutic implication for diabetic cardiomyopathy.